Identificación de parásitos gastrointestinales en ganado bravo, su correspondiente prevención y control en el sector Pachosalag del cantón Latacunga, Provincia de Cotopaxi. - Venegas Quinatoa, Joselyn Rubí (2022)
The present investigation was carried out in the Pachosalag sector of the Latacunga canton, province of Cotopaxi, parish of Tanicuchí, from April to August 2022, with the aim of identifying the gastrointestinal parasites present in the cattle ranches, with the purpose of evaluating the body condition and proposing a deworming protocol for the control and prevention of parasitosis in these cattle ranches. With the collection of 60 samples in gynecological check-up gloves directly from the rectum of the animals, identified and transported at a temperature of 4°C in a cooler, for coproparasitological analysis in the parasitology laboratory of the UTC using the flotation technique with sugar solution (Sheather's). The research was exploratory - descriptive with a quantitative approach. The variables analysed in the study were age and sex. When analysing the data collected, 39 samples were positive (65%) for the presence of gastrointestinal parasites and 21 were negative (35%) respectively. The results of the individual prevalence of parasites are Haemonchus with 7 infected animals (11.7%); Oesophagostomum 8 infected animals (13.3%); Eimeria 11 infected animals (18.3%); Toxocara 4 infected animals (6.7%) and Cooperia 9 infected animals (15%). At the same time, according to the evaluation of the level of CC in the sampled animals, 29 are in the "thin" category, being more affected by the presence of gastrointestinal parasites. Finally, with the analysis of the data collected, the deworming protocol will be based on the application of Albendazole, Sulfas and supplementing the diet of the fighting cattle with mineral salts and vitamins.